High-temperature-resistant inorganic coating prepared from metallurgical solid waste, preparation method and application of high-temperature-resistant inorganic coating, and composite structure
By using metallurgical solid waste to prepare high-temperature resistant inorganic coatings, the dual activation process of grinding + alkali excitation and high-temperature resistant additives are used to solve the shortcomings of existing coatings in high-temperature resistance, water resistance and construction performance, and the high-value utilization of metallurgical solid waste and the high-performance application of coatings are achieved.
Patent Information
- Application Number
- CN202510358505.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing geological polymer-based inorganic coatings have shortcomings in high temperature resistance, water resistance and construction properties, and are difficult to be used in high temperature resistance fields above 400°C.
By using metallurgical solid waste (slag powder and steel slag particles), high temperature resistant inorganic coatings are prepared, and a double activation process of grinding + alkali excitation and high temperature resistant additives are used to generate geopolymer-active mineral powders with high specific surface area and low median particle size, and mixed with inorganic binders and inorganic fillers to form high temperature resistant inorganic coatings.
The high-value utilization of metallurgical solid waste has been realized, and the high-temperature resistance, water resistance and construction performance of the coating have been improved, making it suitable for high-temperature fields above 400℃.
Smart Images

Figure CN119859050A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of inorganic coatings, and in particular to a high-temperature resistant inorganic coating prepared by utilizing metallurgical solid waste, a preparation method and application thereof, and a composite structure. Background Art
[0002] In recent years, the market sales of metallurgical solid waste derivatives such as steel slag and slag powder, which are used as cement raw materials, have declined, which will lead to a significant increase in inventory and overcapacity pressure. Therefore, it is very important to develop high-value-added products based on steel slag and slag powder and explore new ways of consumption. On the other hand, the steel industry generally uses traditional organic coatings for steel structure corrosion protection, which have many problems such as poor corrosion resistance, high temperature resistance, poor weather resistance, high cost, release of harmful substances such as volatile organic compounds (VOCs), flammability, and high transportation and storage costs. Compared with organic coatings, inorganic coatings are a type of coating that uses inorganic materials as film-forming substances. Their raw materials are usually taken from nature and are widely available. They have the advantages of being non-toxic, harmless, long service life, high temperature resistance, and corrosion resistance. The development of green, environmentally friendly, economical and safe high-performance inorganic coatings is an important development direction.
[0003] Geopolymer-based inorganic coatings are a new type of inorganic coatings that use geopolymers as the main film-forming material. In the existing technical system, the silica-alumina raw materials of inorganic gelling materials in these geopolymer-based inorganic coatings are usually (meta) kaolin, fly ash, silicate cement, silica fume, mullite, etc. However, due to the use of sodium-based alkali activators and the poor density of geopolymer coatings, inorganic coatings prepared from such raw materials often have problems such as poor water resistance, easy alkali return, and powdering. In addition, traditional geopolymer inorganic coatings also have problems such as poor film-forming properties, poor leveling and poor construction properties. They often need to add organic film-forming materials such as acrylic emulsions and silicone-acrylic emulsions, which reduces the weather resistance and high temperature resistance of geopolymer inorganic coatings, making it difficult to apply them to high temperature resistant fields, especially those above 400°C.
[0004] Therefore, how to provide a geopolymer inorganic coating that can effectively utilize metallurgical solid waste and at the same time has excellent high temperature resistance, water resistance, good leveling and construction performance has become a problem that needs to be solved urgently. Summary of the invention
[0005] In view of the problems and shortcomings in the prior art, the embodiments of the present invention provide a high-temperature resistant inorganic coating prepared using metallurgical solid waste, a preparation method and application thereof, and a dual anti-corrosion composite structure.
[0006] On the one hand, the method for preparing a high-temperature resistant inorganic coating using metallurgical solid waste provided in an embodiment of the present invention includes: preparing a geopolymer active mineral powder, including: providing a first raw material, the first raw material including: metallurgical solid waste, a silicon regulator, an aluminum regulator, an alkali activator, a high-temperature resistant additive and a composite grinding aid, wherein the metallurgical solid waste includes slag powder and steel slag particles, the steel slag particles contain free calcium oxide and magnesium oxide, and the alkali activator includes silicate and potassium hydroxide but does not include sodium element; mixing and grinding the first raw material to expose the calcium ions and magnesium ions in the free calcium oxide and magnesium oxide, and the composite grinding aid disperses and complexes the calcium ions and magnesium ions, so that the calcium ions and magnesium ions react chemically with the alkali activator to generate silicates in situ, thereby obtaining a geopolymer active mineral powder with a free calcium oxide and magnesium oxide content of less than 1%, and the specific surface area of the geopolymer active mineral powder is greater than 500m 2 / kg, and the median particle size D50 is less than or equal to 5 microns; preparation of an inorganic binder, comprising: providing a second raw material and mixing to obtain an inorganic binder primary product, the second raw material comprising a first component, silica sol and nano zirconium oxide, wherein the first component is selected from potassium water glass or potassium lithium silicate; stabilizing the inorganic binder primary product with an organic silicon liquid to reduce the active silanol groups contained in the inorganic binder primary product, thereby obtaining an inorganic binder; and mixing and stirring the geopolymer active mineral powder, the inorganic binder with an inorganic filler, a function regulating additive and water to obtain a high temperature resistant inorganic coating.
[0007] In one embodiment of the present invention, the mass proportions of the first raw material are as follows: 15-20 parts of the slag powder, 40-55 parts of the steel slag particles, 8-12 parts of the silicon regulator, 3-5 parts of the aluminum regulator, 12 parts of the alkali activator, 5 parts of the high temperature resistant additive and 2-4 parts of the composite grinding aid.
[0008] In one embodiment of the present invention, the mass ratio of silicate to potassium hydroxide in the alkaline activator is (2-4):1, and the silicate in the alkaline activator is selected from potassium silicate, lithium silicate or potassium lithium silicate; the composite grinding aid includes at least one of aluminum sulfate, calcium formate and triethanolamine.
[0009] In one embodiment of the present invention, the mass fractions of the second raw material are as follows: 25 parts of the first component, 72 parts of the silica sol and 3 parts of the nano zirconium oxide.
[0010] In one embodiment of the present invention, the inorganic binder initial product is stabilized by using an organosilicon liquid to reduce the active silanol groups contained in the inorganic binder initial product, specifically comprising: placing the inorganic binder initial product in a container equipped with a reflux device and heating it to 50°C~60°C, adding the organosilicon liquid to the container while stirring, stirring at a constant temperature for a preset time, and then adding water to dilute the solution to an effective solid content of 30% to obtain the inorganic binder.
[0011] In one embodiment of the present invention, the high temperature resistant additive comprises mullite whiskers and nano-titanium dioxide, and the mass ratio of the mullite whiskers to the nano-titanium dioxide is 3:1; the mixing and grinding of the first raw material specifically comprises: mixing the metallurgical solid waste, the silicon regulator, the aluminum regulator, the alkali activator, the high temperature resistant additive and the composite grinding aid and then grinding to generate an Al-O-Si-O-Ti bonding structure, thereby obtaining the geopolymer active mineral powder, wherein the content of the Al-O-Si-O-Ti bonding structure is 1%~3%.
[0012] In one embodiment of the present invention, the particle size of the nano titanium dioxide is 10 to 20 nanometers; the providing of the first raw material includes: organically modifying the nano titanium dioxide using a silane coupling agent; or mixing the nano titanium dioxide and the mullite whiskers to obtain a first mixture, and placing the first mixture in a disperser for dispersion.
[0013] On the other hand, an embodiment of the present invention provides a high-temperature resistant inorganic coating prepared using metallurgical solid waste, which is prepared using any of the aforementioned methods.
[0014] On the other hand, an embodiment of the present invention provides a dual anti-corrosion composite structure, including a steel structure and a composite coating, wherein the composite coating is formed by coating the high-temperature resistant inorganic coating prepared by any of the aforementioned methods on the surface of the steel structure, the surface of the steel structure contains iron hydroxyl defects and oxygen vacancy defects, and the composite coating is bonded to the iron hydroxyl defects and the oxygen vacancy defects on the surface of the steel structure.
[0015] On the other hand, an embodiment of the present invention provides an application of the high-temperature resistant inorganic coating prepared by any of the aforementioned methods in corrosion protection of steel structures.
[0016] It can be seen from the above that the above technical features of the present invention can have one or more of the following beneficial effects: 1. The raw materials of the high-temperature resistant inorganic coating prepared in the embodiment of the present invention include metallurgical solid waste, which is slag and steel slag, so that the metallurgical solid waste is consumed and revalued, and the high-value application of metallurgical solid waste is realized; in addition, the high-temperature resistant characteristics of slag and steel slag can be fully utilized by using the dual activation process of grinding + alkali excitation and high-temperature resistant additives. Compared with the existing scheme using kaolin, fly ash, silicate cement, etc., the prepared inorganic coating has better high-temperature resistance; 2. In the embodiment of the present invention, the raw materials of the geopolymer active mineral powder are mixed and ground. On the one hand, the mechanical grinding method can fully expose the silicon-aluminum active sites (SiO2, Al2O3, etc.) in the steel slag particles and slag powder, and then react with the alkaline activator in situ, which can fully activate the geopolymer activity of the steel slag particles and slag powder (generating SiO3 2- 、Si(OH)4、AlO 2- etc.), thereby obtaining geopolymer active mineral powder with higher activity; 3. The embodiments of the present invention mix and grind the raw materials of the geopolymer active mineral powder. On the other hand, mechanical grinding can expose the calcium ions and magnesium ions in the free calcium oxide and magnesium oxide contained in the steel slag particles. The composite grinding aid can disperse and complex the calcium ions and magnesium ions, so that the calcium ions and magnesium ions react chemically with the alkali activator to generate silicate in situ, thereby reducing the content of free calcium oxide and magnesium oxide in the geopolymer active mineral powder, avoiding the situation that the free calcium oxide and magnesium oxide will hydrate and expand to affect the stability, and solving the problem of poor stability of the geopolymer. 4. The embodiment of the present invention designs the specific surface area and median particle size of the geopolymer active mineral powder to improve the reactivity and stability of the geopolymer active mineral powder; 5. The embodiment of the present invention selects an alkaline activator including silicate and potassium hydroxide but not including sodium element, which can, on the one hand, help to activate the silicon-aluminum raw materials (metallurgical solid waste, silicon regulator, aluminum regulator) to form geopolymers, and the silicate in the alkaline activator can react in situ with the calcium ions and magnesium ions in the free calcium oxide and magnesium oxide contained in the steel slag particles to help solve the stability problem of the steel slag particles; on the other hand, since sodium ions have strong hygroscopicity and are easy to return to the coating surface, by reducing the sodium element in the alkaline activator, it is possible to avoid the sodium ions from absorbing water and generating sodium carbonate with carbon dioxide in the air, thereby improving the water resistance and weathering resistance of the finally obtained high temperature resistant inorganic coating; 6. In the embodiment of the present invention, potassium water glass or potassium lithium silicate is compounded with silica sol, which can reduce the alkalinity and sodium ion content of the inorganic binder on the one hand, so as to reduce the risk of the high temperature resistant inorganic coating having the problems of alkali return, salting out, whitening, fading and floweriness when in contact with water, thereby improving the water resistance, scrub resistance and weather resistance of the high temperature resistant inorganic coating; on the other hand, the good leveling property of silica sol can be used to improve the construction performance and coating appearance of the high temperature resistant inorganic coating, and can also reduce the curing shrinkage stress of the coating generated by the high temperature resistant inorganic coating, improve the adhesion of the coating, thereby reducing the risk of powdering and cracking of the coating generated by the high temperature resistant inorganic coating, so that the high temperature resistant inorganic coating can be applied to more substrates; 7. In the embodiment of the present invention, nano-zirconia is selected as a raw material to prepare an inorganic binder, and the hydroxyl groups on the surface of the nano-zirconia and the silanol groups of the silica sol can be used to form Zr-O-Si bonds to enhance the cross-linking density and form a more stable three-dimensional network structure, thereby enhancing the mechanical properties and thermal stability of the obtained high-temperature resistant inorganic coating; 8. The embodiment of the present invention stabilizes the initial product of the inorganic binder to reduce the active silanol groups contained in the initial product of the inorganic binder, thereby avoiding precipitation and premature coagulation caused by excessive active silanol groups. On the other hand, the stabilization treatment can introduce organic groups, so that the steric hindrance of the organic groups can be used to reduce the condensation activity of the silica sol, thereby greatly improving the stability of the silica sol, reducing the low shear viscosity of the final high-temperature resistant inorganic coating, and improving the leveling performance of the high-temperature resistant inorganic coating.
[0017] 9. The high temperature resistant inorganic coating prepared in the embodiment of the present invention can be applied to steel structures to provide dual corrosion protection. On the one hand, the high temperature resistant inorganic coating can be chemically bonded to the surface of the steel structure to form a strong coating, thereby achieving physical isolation and corrosion protection on the surface of the steel structure; on the other hand, since iron-based materials will undergo electrochemical corrosion in the natural environment to generate hydroxide ions, the silica sol in the high temperature resistant inorganic coating can dissolve the hydroxide to prevent the continuous increase in pH, thereby preventing the continuous electrochemical corrosion of the iron surface by hydroxide, and the cation exchange in the silica sol can prevent hydrogen ion corrosion, thereby achieving electrochemical corrosion protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0019] Figure 1A schematic flow chart of a method for preparing a high temperature resistant inorganic coating using metallurgical solid waste provided in an embodiment of the present invention.
[0020] Figure 2 Another schematic flow chart of a method for preparing a high temperature resistant inorganic coating using metallurgical solid waste provided in an embodiment of the present invention.
[0021] Figure 3 Another schematic flow chart of the method for preparing high temperature resistant inorganic coating using metallurgical solid waste provided in an embodiment of the present invention.
[0022] Figure 4 It is the reaction formula of the initial product of inorganic binder and organic silicon liquid.
[0023] Figure 5 Schematic diagram of the reaction principle of double anti-corrosion.
[0024] Figure 6 This is a comparison chart of the high temperature resistance test results of the experimental examples of the present invention and the comparative examples.
[0025] Figure 7 Schematic diagram of the structure of a double anti-corrosion composite structure. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0028] It should also be noted that the division of multiple embodiments in the present invention is only for the convenience of description and should not constitute a special limitation. The features in various embodiments can be combined and referenced to each other without contradiction.
[0029] See also Figure 1 The present invention provides a method for preparing a high temperature resistant inorganic coating using metallurgical solid waste, for example, comprising the steps of: S12: Preparation of geopolymer active mineral powder; S14: Preparation of inorganic binder; S16: Mixing and stirring the geopolymer active mineral powder, the inorganic binder and inorganic filler, the function regulating auxiliary agent and water to obtain a high temperature resistant inorganic coating.
[0030] For details, see Figure 2 , step S12 specifically includes: S122: providing a first raw material; S124: Grinding the first raw material to expose the free calcium ions and magnesium ions in the calcium oxide and magnesium oxide, disperse and complex the calcium ions and magnesium ions by the composite grinding aid, and react the calcium ions and magnesium ions with the alkali activator to generate silicate in situ, thereby obtaining a geopolymer active mineral powder with a free calcium oxide and magnesium oxide content of less than 1%.
[0031] Wherein, in step S122, the first raw material includes, for example, metallurgical solid waste, silicon regulator, aluminum regulator, alkali activator, high temperature resistant additive and composite grinding aid, wherein the metallurgical solid waste includes, for example, slag powder and steel slag particles, wherein the steel slag particles contain free calcium oxide and magnesium oxide, and the alkali activator includes silicate and potassium hydroxide but does not include sodium element. The slag powder mentioned above is, for example, the abbreviation of granulated blast furnace slag powder, which is a high-quality concrete admixture, which is obtained by drying and grinding granulated blast furnace slag that meets the GB / T203 standard to reach a powder with a considerable fineness and a considerable activity index, wherein the granulated blast furnace slag is a melt with calcium silicate as the main component obtained by the iron smelting plant when smelting pig iron in the blast furnace, and the industrial solid waste slag is obtained after water quenching and granulation. For example, the slag powder is, for example, S95 grade or above, and the whiteness of the slag powder is above 85. The steel slag particles mentioned above are, for example, steel slag crushed into particles of 3 to 5 mm by a roller press or a vertical mill, and the steel slag is, for example, steel smelting slag obtained by water-spraying suffocating slag, wind-quenching slag or other similar methods. Among them, the steel slag particles contain, for example, free calcium oxide and magnesium oxide. The silicon regulator mentioned above is, for example, selected from one or more of silica ash, high silica, and quartz powder, and the aluminum regulator is, for example, α-alumina. Alkali activators include, for example, silicates and potassium hydroxide, but the alkaline activator does not include sodium. The high-temperature resistant additives mentioned above include mullite whiskers and nano-titanium dioxide. In addition, the composite grinding aid includes at least one of aluminum sulfate, calcium formate and triethanolamine. It should be noted that steel slag particles and slag powder are siliceous and aluminum raw materials, that is, the main raw materials for the high-temperature resistant inorganic coating to be prepared in the embodiment of the present invention. Silicon regulator and aluminum regulator are also silicon-aluminum raw materials. Since the content of silicon and aluminum in metallurgical solid waste (steel slag particles and slag powder) will fluctuate, silicon regulator and aluminum regulator are added to regulate the content of SiO2 and Al2O3 in steel slag particles and slag powder. Alkali activators can help stimulate the formation of geopolymers from silicon-aluminum raw materials and quickly generate silicates in situ from unstable components such as free calcium oxide and magnesium oxide in steel slag particles to improve stability. High temperature resistant additives can further improve the high temperature resistance of steel slag particles and slag powder. Composite grinding aids mainly have the functions of grinding aid and dispersion aid, and can also complex and disperse calcium ions and magnesium ions in free calcium oxide and magnesium oxide to facilitate the reaction of alkaline activators with them.
[0032] By using metallurgical solid waste as raw materials to prepare high-temperature resistant inorganic coatings, metallurgical solid waste is consumed and revalued, realizing the high-value application of metallurgical solid waste. In addition, the high-temperature resistant properties of slag and steel slag can be fully utilized through the dual activation process of grinding + alkali activation and high-temperature resistant additives. Compared with the existing solutions using kaolin, fly ash, silicate cement, etc., the prepared inorganic coating has better high-temperature resistance.
[0033] Preferably, the mass proportions of the first raw material are as follows: 15-20 parts of the slag powder, 40-55 parts of the steel slag particles, 8-12 parts of the silicon regulator, 3-5 parts of the aluminum regulator, 12 parts of the alkali activator, 5 parts of the high temperature resistant additive and 2-4 parts of the composite grinding aid. Such a proportion can obtain a geopolymer active mineral powder with good performance.
[0034] Furthermore, the mass ratio of silicate to potassium hydroxide in the alkaline activator is, for example, (2-4):1, and the silicate in the alkaline activator is, for example, selected from potassium silicate, lithium silicate or potassium lithium silicate. By selecting the above alkaline activator, on the one hand, it can help to stimulate the silicon-aluminum raw materials (metallurgical solid waste, silicon regulator, aluminum regulator) to form geopolymers, and react in situ with calcium ions and magnesium ions in free calcium oxide and magnesium oxide contained in steel slag particles to help solve the stability problem of steel slag particles; on the other hand, since sodium ions have strong hygroscopicity and are easy to return to the coating surface, by reducing the sodium element in the alkaline activator, it can be avoided that the sodium ions absorb water and generate sodium carbonate with carbon dioxide in the air, so that the water resistance and weathering resistance of the finally obtained high temperature resistant inorganic coating can be improved.
[0035] According to the above, in step S124, the first raw material is put into a ball mill for mixing and grinding to obtain a geopolymer active mineral powder having a free calcium oxide and magnesium oxide content of less than 1%, wherein the specific surface area of the geopolymer active mineral powder is greater than 500m 2 / kg, and the median particle size D50 is less than or equal to 5 microns, and the specific surface area and median particle size of the geopolymer active mineral powder are designed to improve the reactivity and stability of the geopolymer active mineral powder. For example, the above physical properties of the geopolymer active mineral powder can be achieved by adding grinding aids, matching steel balls and steel forgings in the ball mill, and controlling the ball milling time. The mixing time of each batch of materials is, for example, not less than 1 hour.
[0036] By mixing and grinding the raw materials of geopolymer active mineral powder, the mechanical grinding method can fully expose the silicon-aluminum active sites (SiO2, Al2O3, etc.) in the slag particles and slag powder, and then react with the alkali activator in situ, which can fully activate the geopolymer activity of the slag particles and slag powder (generating SiO3 2- 、Si(OH)4、AlO 2-On the other hand, mechanical grinding can expose the calcium ions and magnesium ions in the free calcium oxide and magnesium oxide contained in the steel slag particles. The composite grinding aid can disperse and complex the calcium ions and magnesium ions, so that the calcium ions and magnesium ions react chemically with the alkali activator to generate silicate in situ, thereby reducing the content of free calcium oxide and magnesium oxide in the geopolymer active mineral powder, avoiding the situation where the free calcium oxide and magnesium oxide will hydrate and expand to affect the stability, and solving the problem of poor stability of the geopolymer.
[0037] See also Figure 3 , step S14 for example includes: S142: providing a second raw material and mixing it to obtain a primary inorganic binder product; S144: Stabilizing the inorganic binder product using an organic silicon liquid to reduce the active silanol groups contained in the inorganic binder product, thereby obtaining an inorganic binder.
[0038] Specifically, the second raw material in step S142 includes, for example, the first component, silica sol and nano zirconium oxide, wherein the first component is selected from potassium water glass or potassium lithium silicate. The mass fractions of the second raw material are as follows: 25 parts of the first component, 72 parts of the silica sol and 3 parts of the nano zirconium oxide. The inorganic binder prepared by the above ratio is alkaline, and its pH range can be adjusted, so that the alkaline activator required for the active mineral of the geopolymer can be further supplemented. After the second raw material is mixed according to the above mass fractions, it is placed in a shearing machine for shearing and stirring for 20 minutes to obtain the initial product of the inorganic binder. For example, the modulus of potassium water glass is 3.5~4.0, the solid content is 35~40%, and the pH is 11-13. Potassium water glass has quick drying performance and good water resistance, and potassium water glass is not easy to return to alkali, so that no visible whitening will be generated on the surface of the coating. In addition, potassium water glass has a higher melting temperature and better fire resistance, so that a better high-temperature resistant inorganic coating can be obtained. In some specific embodiments, for example, potassium lithium silicate (molecular formula xLi2O·yK2O·mSiO2) can be used, with a modulus of 4-5 and a solid content of 35-40%. It is a composite of potassium silicate and lithium silicate, and has both performance advantages and price cost advantages. It is cost-effective and suitable for use in dark-colored mid-to-high-end coatings. In addition, the silica sol mentioned above is, for example, a high-purity nano-scale silica sol with a particle size of 8-15 nanometers, a solid content of 30%, and a pH of 7.5-9.5. The nano-zirconia mentioned above refers to, for example, nano-zirconium dioxide. For example, the particle size of nano-zirconium oxide is usually between 1 and 100 nanometers.
[0039] By compounding potassium water glass or potassium lithium silicate with silica sol, on the one hand, the alkalinity and sodium ion content of the inorganic binder can be reduced to reduce the risk of the high temperature resistant inorganic coating having problems such as alkali return, salting out, fading and floweriness when in contact with water, thereby improving the water resistance, scrub resistance and weather resistance of the high temperature resistant inorganic coating; on the other hand, the good leveling property of silica sol can be used to improve the construction performance and coating appearance of the high temperature resistant inorganic coating, and can also reduce the curing shrinkage stress of the coating produced by the high temperature resistant inorganic coating, improve the adhesion of the coating, thereby reducing the risk of powdering and cracking of the coating produced by the high temperature resistant inorganic coating, so that the high temperature resistant inorganic coating can be applied to more substrates. In addition, by selecting nano zirconium oxide as a raw material to prepare an inorganic binder, the hydroxyl group on the surface of nano zirconium oxide and the silanol group of silica sol can be used to form a Zr-O-Si bond, and the reaction formula is as follows: Zr-OH + HO-Si → Zr-O-Si + H2O.
[0040] By forming Zr-O-Si bonds, nano zirconium oxide can be used as a cross-linking promoter in the silica sol system, providing additional cross-linking points, enhancing the cross-linking density of the system, and forming a more stable three-dimensional network structure, thereby enhancing the mechanical properties and thermal stability of the obtained high-temperature resistant inorganic coating. For example, the high-temperature resistant inorganic coating with the addition of nano zirconium oxide can achieve the effect of resistance to rapid cooling and heating at 800°C. The rapid cooling and heating mentioned here is, for example, a rapid cooling and heating experiment, which is a method for quickly verifying the high performance resistance of the coating. The specific experimental method is: put the sprayed coating test plate into a muffle furnace at the corresponding temperature and bake it for 2 hours, then take it out and put it directly into room temperature water for cooling.
[0041] Furthermore, step S144 specifically includes: placing the initial product of the inorganic binder in a container equipped with a reflux device and heating it to 50°C~60°C, adding the silicone liquid into the container while stirring, stirring at a constant temperature for a preset time, and then adding water to dilute the solution to an effective solid content of 30% to obtain the inorganic binder.
[0042] Among them, the above-mentioned organosilicon liquid refers to, for example, a liquid form with polysiloxane (such as polydimethylsiloxane, PDMS) as the main component. The main chain of the organosilicon liquid is composed of silicon-oxygen bonds (-Si-O-Si-), and organic groups (such as methyl) are connected to the silicon atoms. It has low viscosity, low surface tension and good chemical stability. The above-mentioned container equipped with a reflux device refers to, for example, a three-necked flask equipped with a reflux device, and the above-mentioned preset time is, for example, 6 hours. The above-mentioned effective solid content is, for example, the solid content of the inorganic binder. After the above-mentioned stabilization treatment, the number of active silanol groups contained in the initial product of the inorganic binder is reduced to 30%~50% of the original.
[0043] Specifically, since the initial product of the inorganic binder contains a large number of active silanol groups, it is prone to polycondensation and precipitation and premature coagulation. In the embodiment of the present invention, the initial product of the inorganic binder is stabilized by an organic silicon liquid to reduce the active silanol groups contained in the initial product of the inorganic binder, thereby avoiding precipitation and premature coagulation caused by an excessive number of active silanol groups; on the other hand, the stabilization treatment can introduce organic groups, so that the steric hindrance of the organic groups can be used to reduce the activity of the silica sol in polycondensation, thereby greatly improving the stability of the silica sol. For example, the reaction formula of the initial product of the inorganic binder and the organic silicon liquid is shown in FIG. Figure 4 , Figure 4 RSi(OCH3)3 in it is, for example, an organic silicon liquid, and R is, for example, CH3 or C4H9. The -Si-OH on the surface of the initial product of the inorganic binder can react with the organic silicon liquid to generate an inorganic binder having a -Si-O-Si-R- structure, thereby increasing and reducing the number of silanol groups, thereby improving the stability of the inorganic binder.
[0044] Therefore, the inorganic binder that has been stabilized can significantly improve the stability while retaining certain active groups, especially it can prevent the active groups from prematurely undergoing dehydration condensation and self-polymerization reaction, and the viscosity is more stable when mixed with pigments and fillers, preventing the early setting phenomenon. In addition, due to the introduction of organic groups, the low shear viscosity of the coating is reduced, thereby improving the leveling performance of the coating.
[0045] Based on the above, in step S16, the geopolymer active mineral powder, inorganic binder and inorganic filler, function regulating additive and water are mixed and stirred uniformly to obtain a high temperature resistant inorganic coating.
[0046] By combining inorganic binders and geopolymer active mineral powders, the following advantages are achieved: ① The adhesion of high temperature resistant inorganic coatings is improved, thereby reducing the curing shrinkage stress of the coating generated by the high temperature resistant inorganic coatings, and reducing the risk of powdering and cracking of the coatings, making the high temperature resistant inorganic coatings suitable for more substrates. The use of organic film-forming materials or organic binders is avoided, so that the high temperature resistance and aging resistance of the high temperature resistant inorganic coatings will not be affected by organic matter.
[0047] ② The density of the coating generated by the high temperature resistant inorganic coating is improved, thereby improving the anti-fouling and water resistance of the high temperature resistant inorganic coating.
[0048] ③ A high-temperature resistant inorganic coating prepared from geopolymer active mineral powder and an inorganic binder constructed from silica sol and potassium water glass / potassium lithium silicate, which can generate a composite coating containing active silanol groups and silicates (such as iron silicate, aluminum silicate, aluminum iron silicate, etc.), which can bond with defects on the surface of steel structures. Specifically, defects on the surface of steel structures include, for example, iron hydroxyl defects (Fe-OH defects) and oxygen vacancy defects (Fe=O defects). The composite coating can bond with the above defects to form chemical bonds such as Fe-O-Fe, Fe-O-Si and Fe-O-Al, so that the composite coating forms excellent adhesion on the surface of steel structures, so that the high-temperature resistant inorganic coating can be used as an anti-corrosion for steel structures. Specifically, for example, the high-temperature resistant inorganic coating has a dual anti-corrosion effect on steel structures. For example, the specific reaction principle diagram of the dual anti-corrosion can be found in the attached Figure 5 On the one hand, high temperature resistant inorganic coatings can form a strong coating with the surface of steel structure through chemical bonding, thereby achieving physical isolation and corrosion protection on the surface of steel structure parts; on the other hand, electrochemical corrosion protection. For example, see Figure 5 Since iron-based materials will undergo electrochemical corrosion in the natural environment and generate hydroxide ions, the silica sol in the high-temperature resistant inorganic coating can dissolve the hydroxide to prevent the continuous increase in pH, thereby preventing the continuous electrochemical corrosion of the iron surface by hydroxide, and the cation exchange in the silica sol (such as the exchange of calcium ions and hydrogen ions) can prevent hydrogen ion corrosion. In this way, electrochemical corrosion protection can be achieved.
[0049] In addition, in a specific embodiment, the high temperature resistant additive includes mullite whiskers and nano titanium dioxide, and the mass ratio of the mullite whiskers to the nano titanium dioxide is 3:1. Nano titanium dioxide is, for example, nano-grade titanium dioxide, and the particle size of nano titanium dioxide is usually 1 to 100 nanometers. Nano titanium dioxide can absorb ultraviolet rays, reflect and scatter ultraviolet rays, and is an ultraviolet protection agent with excellent performance. Adding nano titanium dioxide to the coating can improve the aging resistance of the coating and prevent the degradation of the coating performance caused by ultraviolet radiation. Among them, the main bonding structure in the silicon-aluminum raw material composed of metallurgical solid waste, silicon regulator, and aluminum regulator is [O-Si-O-Al]. By introducing a high temperature resistant functional additive composed of mullite whiskers and nano titanium dioxide for mixing and grinding, a [Al-O-Si-O-Ti] bonding structure is generated, thereby further improving the high temperature resistance of the high temperature resistant inorganic coating.
[0050] Specifically, step S124 specifically includes: mixing the metallurgical solid waste, the silicon regulator, the aluminum regulator, the alkali activator, the high temperature resistant additive and the composite grinding aid, and then grinding to generate an Al-O-Si-O-Ti bonding structure, thereby obtaining the geopolymer active mineral powder, wherein the content of the Al-O-Si-O-Ti bonding structure is 1% to 3%. The introduction of the Al-O-Si-O-Ti bonding structure can improve the high temperature resistance of the high temperature resistant inorganic coating. For example, after adding the high temperature resistant additive, the high temperature resistant inorganic coating undergoes multiple 800°C rapid cooling and heating tests, and the coating generated by the coating remains intact. However, the coating without the addition of the high temperature resistant additive will crack or powder after generally undergoing a 300°C rapid cooling and heating test.
[0051] It should be noted that, due to the high activity of nano-titanium dioxide and its easy aggregation, it is necessary to firstly perform organic modification or effective dispersion treatment on it when using it with mullite whiskers to form a high temperature resistant additive. For example, providing a first raw material, for example, includes: using a silane coupling agent to perform organic modification treatment on the nano-titanium dioxide. Among them, the particle size of nano-titanium dioxide is 10 to 20 nanometers. The above-mentioned silane coupling agent is a class of organic silicon compounds with a special structure, which can establish chemical bonds between inorganic materials (such as glass, metal, ceramics, fillers) and organic materials (such as resins, rubbers, plastics), thereby significantly improving the interfacial bonding force, mechanical properties and durability of composite materials. The general formula of the molecular structure of the silane coupling agent is: Y-R-Si-X3, where Y is an organic functional group (such as amino, epoxy, vinyl, thiol, etc.), which can react with organic materials (such as resins, rubbers); R is a short-chain alkyl (such as -CH2CH2-), as a connecting group. X is a hydrolyzable group (such as methoxy, ethoxy, chloro, etc.), which generates silanol (-Si-OH) after hydrolysis and combines with the surface of inorganic materials. The above-mentioned organic modification treatment is, for example, to react silane coupling agent with nano-titanium dioxide. In this way, the agglomeration of nano-titanium dioxide can be avoided.
[0052] Alternatively, providing a first raw material includes, for example, mixing the nano titanium dioxide and the mullite whisker to obtain a first mixture, and placing the first mixture in a disperser for dispersion treatment. For example, the disperser mentioned here is, for example, a high-speed disperser, and its speed is, for example, greater than 2000 revolutions per minute. Here, for example, the nano titanium dioxide and the mullite whisker are mixed and immediately placed in a disperser for dispersion treatment. In this way, agglomeration of the nano titanium dioxide is avoided.
[0053] In addition, in a specific embodiment, step S16 specifically includes: mixing and stirring the geopolymer active mineral powder, the inorganic binder and the inorganic filler, the function regulating additive, the inorganic pigment and water to obtain a high temperature resistant inorganic coating.
[0054] Among them, the inorganic fillers mentioned above include one or more of heavy calcium powder, quartz sand, quartz powder or silicon powder, diatomaceous earth, bentonite, titanium dioxide, barite powder and barium sulfate. Heavy calcium powder, for example, has excellent filling performance, and the main component of quartz powder is SiO2, which has good stability and can improve the strength and weather resistance of the high temperature resistant geopolymer inorganic coating after film formation. Bentonite can increase the consistency of the high temperature resistant geopolymer inorganic coating, thereby improving the suspension of the high temperature resistant geopolymer inorganic coating, and improving its anti-settling and leveling properties. Titanium dioxide can improve the hiding power, weather resistance and light resistance of the high temperature resistant geopolymer inorganic coating, and improve the mechanical strength of the high temperature resistant geopolymer inorganic coating coating. Barite powder can improve the wear resistance and scratch resistance of the high temperature resistant geopolymer inorganic coating. By adding the above-mentioned inorganic fillers, the various physical and chemical properties of the high temperature resistant geopolymer inorganic coating can be further mentioned.
[0055] The functional adjustment additives mentioned above include dispersants, water reducing agents, thickeners, hydrophobic agents, leveling agents and defoamers. For example, the dispersant is dispersant 5040, which can significantly improve the dispersibility, stability and overall performance of the high temperature resistant geopolymer inorganic coating. The water reducing agent is a polycarboxylic acid type high efficiency water reducing agent, which can reduce the water demand during the formation of geopolymers, thereby increasing the compactness of the high temperature resistant geopolymer inorganic coating. The thickener is a cellulose ether or a heteropolysaccharide, preferably a polyanionic cellulose ether, which can improve the leveling performance of the high temperature resistant geopolymer inorganic coating. The hydrophobic agent is an aminoalkyl polydimethylsiloxane, which can improve the hydrophobicity, water resistance and air permeability of the high temperature resistant geopolymer inorganic coating. The leveling agent is GT-450, which can improve the leveling performance of the high temperature resistant geopolymer inorganic coating. The defoamer is DF-220S or F-111. Since high temperature resistant geopolymer inorganic coatings introduce air during production, mixing and construction, generating a large number of bubbles, adding a defoaming agent can defoam and improve the density of the coating.
[0056] The inorganic pigments mentioned above include Lithopone or titanium dioxide, iron-based or cobalt-based inorganic pigments. Among them, Lithopone has a lower cost of use than titanium dioxide. Therefore, the use of Lithopone with better cost performance can reduce the production cost of high-temperature resistant geopolymer inorganic coatings while maintaining good hiding power and whiteness. In the use scenario where the temperature is below 200 ℃, for example, iron-based inorganic pigments are selected; in the use scenario where the temperature is above 200 ℃, for example, cobalt-based inorganic pigments are selected. Cobalt-based inorganic pigments have better high-temperature resistance than iron-based inorganic pigments.
[0057] Specifically, step S16 specifically includes: S162: mixing the function regulating auxiliary agent with the water and stirring to obtain an intermediate mixture; S164: adding the geopolymer active mineral, the inorganic filler, the inorganic pigment and the inorganic binder to the intermediate mixture in sequence, and stirring for 15 to 20 minutes to obtain the high temperature resistant inorganic coating.
[0058] By designing the mixing order of various raw materials and water, the obtained high temperature resistant inorganic coating can have better physical and chemical properties. Among them, the Stormer viscosity of the high temperature resistant inorganic coating is 60-70KU, and the prepared high temperature resistant geopolymer inorganic coating has uniform texture and no undesirable phenomena such as water bleeding, stratification, and precipitation.
[0059] To sum up, the high temperature resistant inorganic coating prepared in the embodiment of the present invention comprises metallurgical solid waste in its raw materials, and the metallurgical solid waste is slag and steel slag, thereby absorbing and re-assigning value to the metallurgical solid waste, thereby realizing the high value application of metallurgical solid waste; in addition, the high temperature resistant properties of slag and steel slag can be fully utilized through the dual activation process of grinding + alkali excitation and high temperature resistant additives. Compared with the existing scheme of using kaolin, fly ash, silicate cement, etc., the prepared inorganic coating has better high temperature resistance.
[0060] The present invention is further described in detail below in conjunction with specific embodiments. The embodiments are only used to explain the present invention but not to limit the scope of the present invention.
[0061] Specifically, the high temperature resistant inorganic coating prepared by the above-mentioned method of preparing high temperature resistant inorganic coating using metallurgical solid waste is applied to the surface of steel structure parts to prevent corrosion of steel structure parts, or it can also be applied to the surface of concrete. For example, the prepared high temperature resistant inorganic coating can be brushed or sprayed after being stirred evenly. Preferably, aerodynamic spraying can be used, wherein the air pressure is 0.8Mpa, so as to ensure uniform atomization spraying. The spraying thickness is, for example, 0.6~1.0mm, and there is no obvious leakage, bottom penetration, dripping and other phenomena. In actual use, the surface of inorganic objects to be sprayed, such as concrete, should be flat, solid, tidy, free of floating dust, paint and other dirt. If the object to be sprayed is the surface of a steel structure, its surface is required to reach the secondary power rust removal standard (ST2 level), and no rust removal processes such as sandblasting, shot blasting, and pickling are required. In addition, the use temperature is 5~38℃, and the humidity is less than 85%.
[0062] In order to better illustrate the advantages of the embodiments of the present invention, the high temperature resistant inorganic coating prepared by the embodiments of the present invention was tested for relevant physical and chemical properties. The test methods used in the following experimental examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0063] Experimental object: The high temperature resistant inorganic coating prepared in the embodiment of the present invention is used as an experimental example; the control example is Hannosen high temperature resistant paint.
[0064] 1. High temperature resistance test 1. Experimental method: The above experimental examples and control examples were brushed on the surface of the steel structure substrate, respectively. After curing as required, they were placed in a muffle furnace, set at 500°C, and baked for 8 hours a day.
[0065] 2. Experimental results: See Figure 6 When baked for the third day, the coating of the control example showed cracking and bulging (such as Figure 6 The coating on the left side of the figure is shown in Fig. 2), while the coating in the above experimental example showed no damage (as shown in Fig. Figure 6 coating on the right side of the center).
[0066] 2. Temperature resistance test 1. Experimental method: The steel structure test block sprayed with the above experimental example was placed in a muffle furnace at 800°C for 2 hours, taken out and directly placed in room temperature water, and the experiment was repeated 10 times.
[0067] 2. Experimental results: The coatings in the above experimental examples did not show any cracking, peeling or shedding.
[0068] 3. Freeze-thaw resistance and artificial aging experiments: 1. Experimental method: Place the test piece sprayed with the above experimental example in a low temperature test box at -40℃ for 3 hours, take it out and directly put it in a hot air furnace at 80℃ for 3 hours, and then soak it in room temperature water for 18 hours. This is one cycle, and the experiment should be carried out continuously for more than 10 cycles.
[0069] 2. Experimental results: The coating of the above experimental examples did not fall off, crack or powder.
[0070] 4. Impact resistance test 1. Experimental method: Test the impact resistance of the coating according to the test method for impact resistance of paint film GB / T 1732-2020.
[0071] 2. Experimental results: The coating of the above experimental example has no cracks, no peeling, no falling off, and no wrinkles.
[0072] In addition, the above experimental examples were also tested for water resistance, alkali resistance and salt spray resistance. Among them, the longest time of the salt spray test was 800 hours. The coating of the above experimental examples did not bubble, rust or fall off, and the unidirectional corrosion at the scratch was less than 2mm, which met the requirements of the GB / T1711-2007 standard. The water resistance and alkali resistance of the above experimental examples met the requirements of the standard "Exterior Wall Inorganic Architectural Coatings" (JG / T 26-2002). The coating surface of the above experimental examples can achieve a hydrophobic effect, and the surface is dense and hydrophobic.
[0073] In summary, the high temperature resistant inorganic coating prepared by the above examples fully meets the requirements of high temperature resistance (800°C), freeze-thaw resistance (-40°C), water resistance, alkali resistance, salt spray resistance, etc., and has the advantages of strong adhesion and impact resistance. It should be noted that the freeze-thaw resistance requirement stipulated in the "Architectural Coatings-Determination of Freeze-Thaw Cycle Resistance of Coatings" (JG / T 25-1999) is only -20°C~50°C.
[0074] On the other hand, an embodiment of the present invention further provides a high temperature resistant inorganic coating prepared using metallurgical solid waste, which is prepared, for example, using the aforementioned method for preparing a high temperature resistant inorganic coating using metallurgical solid waste.
[0075] On the other hand, see Figure 7 The embodiment of the present invention also provides a dual anti-corrosion composite structure 30, the composite structure 30 includes a steel structure 32 and a composite coating 31, the composite coating 32 is formed by coating the surface of the steel structure 31 with the high-temperature resistant inorganic coating prepared by the aforementioned method of preparing high-temperature resistant inorganic coating using metallurgical solid waste, the surface of the steel structure 32 contains iron hydroxyl defects and oxygen vacancy defects, and the composite coating 31 is bonded to the iron hydroxyl defects and the oxygen vacancy defects on the surface of the steel structure 32.
[0076] It can be understood that the aforementioned embodiments are merely exemplary descriptions of the present invention. The technical solutions of the various embodiments can be arbitrarily combined and used in combination, provided that the technical features do not conflict, the structures do not contradict, and the purpose of the present invention is not violated.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high temperature resistant inorganic coating using metallurgical solid waste, characterized in that: include: Preparation of geopolymer active mineral powder, including: Providing a first raw material, the first raw material comprising: metallurgical solid waste, silicon regulator, aluminum regulator, alkali activator, high temperature resistant additive and composite grinding aid, wherein the metallurgical solid waste comprises slag powder and steel slag particles, the steel slag particles contain free calcium oxide and magnesium oxide, and the alkali activator comprises silicate and potassium hydroxide but does not include sodium element; The first raw material is mixed and ground to expose the calcium ions and magnesium ions in the free calcium oxide and magnesium oxide, and the composite grinding aid disperses and complexes the calcium ions and magnesium ions, so that the calcium ions and magnesium ions react chemically with the alkali activator to generate silicate in situ, thereby obtaining a geopolymer active mineral powder with a free calcium oxide and magnesium oxide content of less than 1%, and a specific surface area of the geopolymer active mineral powder of more than 500m 2 / kg, and the median particle size D50 is less than or equal to 5 microns; Preparation of inorganic binder, including: Providing a second raw material and mixing them to obtain an inorganic binder primary product, wherein the second raw material comprises a first component, silica sol and nano zirconium oxide, wherein the first component is selected from potassium water glass or potassium lithium silicate; The inorganic binder preliminary product is stabilized by using an organic silicon liquid to reduce the active silanol groups contained in the inorganic binder preliminary product, thereby obtaining an inorganic binder; and The geopolymer active mineral powder, the inorganic binder and inorganic filler, the function regulating auxiliary agent and water are mixed and stirred to obtain a high temperature resistant inorganic coating.
2. The method according to claim 1, characterized in that The mass proportions of the first raw material are as follows: 15-20 parts of the slag powder, 40-55 parts of the steel slag particles, 8-12 parts of the silicon regulator, 3-5 parts of the aluminum regulator, 12 parts of the alkali activator, 5 parts of the high temperature resistant additive and 2-4 parts of the composite grinding aid.
3. The method according to claim 2, characterized in that The mass ratio of silicate to potassium hydroxide in the alkaline activator is (2-4):1, and the silicate in the alkaline activator is selected from potassium silicate, lithium silicate or lithium potassium silicate; the composite grinding aid includes at least one of aluminum sulfate, calcium formate and triethanolamine.
4. The method according to claim 1, characterized in that The mass proportions of the second raw material are as follows: 25 parts of the first component, 72 parts of the silica sol and 3 parts of the nano zirconium oxide.
5. The method according to claim 1, characterized in that The method of stabilizing the inorganic binder primary product by using an organic silicon liquid to reduce the active silanol groups contained in the inorganic binder primary product specifically includes: The initial product of the inorganic binder is placed in a container equipped with a reflux device and heated to 50°C~60°C, and the silicone liquid is added to the container while stirring. After constant temperature stirring for a preset time, water is added to dilute the solution to an effective solid content of 30% to obtain the inorganic binder.
6. The method according to claim 2, characterized in that The high temperature resistant additive comprises mullite whiskers and nano titanium dioxide, and the mass ratio of the mullite whiskers to the nano titanium dioxide is 3:1; The mixing and grinding of the first raw material specifically includes: The metallurgical solid waste, the silicon regulator, the aluminum regulator, the alkali activator, the high temperature resistant additive and the composite grinding aid are mixed and ground to generate an Al-O-Si-O-Ti bonding structure, thereby obtaining the geopolymer active mineral powder, wherein the content of the Al-O-Si-O-Ti bonding structure is 1% to 3%.
7. The method according to claim 6, characterized in that The particle size of the nano titanium dioxide is 10-20 nanometers; the first raw material is provided, including: Using a silane coupling agent to perform organic modification on the nano titanium dioxide; or, The nano titanium dioxide and the mullite whisker are mixed to obtain a first mixture, and the first mixture is placed in a disperser for dispersion treatment.
8. A high temperature resistant inorganic coating prepared using metallurgical solid waste, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the high temperature resistant inorganic coating prepared by the method according to any one of claims 1 to 7 in corrosion protection of steel structures.
10. A dual anti-corrosion composite structure, characterized in that: It comprises a steel structure and a composite coating, wherein the composite coating is formed by coating the high-temperature resistant inorganic coating prepared by the method described in any one of claims 1 to 7 on the surface of the steel structure, the surface of the steel structure contains iron hydroxyl defects and oxygen vacancy defects, and the composite coating is bonded to the iron hydroxyl defects and the oxygen vacancy defects on the surface of the steel structure.
Citation Information
Patent Citations
Geopolymer material-based road marking coating and preparation method thereof
CN111635652A
Inorganic silicate coating and inorganic silicate primer
CN113248949A
Thermal insulation coating as well as preparation method and application thereof
CN114806240A
Graphene oxide and siloxane polymer composite modified geopolymer anticorrosive paint as well as preparation method and application thereof
CN118909470A
Long-lasting, thermally stable coating material for non-absorbent substrates
DE102023108000A1